(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Financial transactions carried out digitally minimise the need for traditional documentation like cheques. Debit cards, credit cards, smart cards, e-wallets, e-cash, electronic cheques, and more are examples of digital payments. The use of digital wallets loaded with deals and coupons is leading in a new era of payment systems.